Mainstream Economics in the Early 21st Century: What, How and How Far (2012)
This essay defines economics as a social science characterized by a particular and evolving way of thinking, and explores its scope and limitations. It is argued that economics has a strong normative nature and that it is ideological by construction. Thus, economics is better suited to improve our understanding of economic phenomena, contribute to solve better current problems and generate a sufficiently large and lasting consensus, than to prove anything for sure. Some reasons for persistent differences among economists are trade-offs, problems measuring economic variables and deficient definitions for key concepts. Thus, economics education should seek constructing explicitly the economics way of thinking and maintaining focus on optimal policy intervention, while its practice should aim at clarity, transparency, tractability, consistency, replicability, applicability, relevance and responsibility.